The naughtiest girl saves the day - Digby, Anne; Blyton, Enid (Hodder Children's Books London, 2014)
When some school strawberry plants are vandalised, a lost blazer button at the scene of the crime leads straight to the Naughtiest Girl. It is hers, but how did it get there - and why would anyone want to pin the blame on Elizabeth?